Weak agreement between the species conservation status assessments of the European Habitats Directive and Red Lists. (June 2016) - Moser, D.; Ellmauer, T.; Evans, D.; Zulka, K.P.; Adam, M.; Dullinger, S.; Essl, F.
Abstract: Public acceptance of conservation measures and measuring the effectiveness of conservation efforts essentially depends on the agreement among experts on the conservation status of species. Here we provide the first European Union-wide comparison of assessments of conservation status of species using two independent frameworks, reports under the European Habitats Directive (HD) and Red Lists. We compared the national and EU-wide conservation status of species assessed for the two last HD reports (2001–2006, 2007–12) with national (27 EU member states) and European Union Red Lists. Discrepancies in species' conservation status assessments of Red Lists and the HD were substantial: the average Spearman correlation coefficient was 0.49 for the first and 0.47 for the second HD report for countries and 0.39 for the first and 0.45 for the second HD report for the whole EU. In addition, correlations differed widely between different EU Member States, with the national assessments of several European countries showing no relationship at all. Surprisingly, many presumably well-known species were assessed very differently. Moreover, there was no evidence of any convergence between the Red Lists and HD reports over time. On average, Red Lists were more pessimistic about the conservation status of species than the HD reports. These low agreements between the two methods raise doubts about the reliability and validity of these assessments and certainly call for a careful revision of the many divergent assessments. Highlights: We compared species' Red List and Habitat's Directive conservation status. European Habitat Directive Reports and Red Lists show only weak correlations. Red Lists are more pessimistic about the conservation status of species. Results call for revision of divergent assessments.